Defense mechanisms in the bovine mammary gland - MAVROGIANNI (Β. Σ. ΜΑΥΡΟΓΙΑΝΝΗ), V. S.; FTHENAKIS (Γ. Χ. ΦΘΕΝΑΚΗΣ), G. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
In the present article the literature on the defence mechanisms of the bovine mammary gland is reviewed. The article is divided into three sections: (i) The teat, (ii) Cellular defence mechanisms (number of somatic cells, type of somatic cells, counting of somatic cells, defence role of somatic cells: macrophages, neutrophils, lymphocytes) and (iii) Chemoral defence mechanisms (cytokines: IL-1, IL-2, IL-8, granulocyte/macrophage-colony stimulating factor and TNF-a, immunoglobulins, complement, lactoferrin, lactoperoxidase/thiocyanate/ H 2 0 2 system, lysozyme).